Uji Aktivitas Antibakteri Dari Air Perasan Bawang Putih Terhadap Bakteri Salmonella Typhi - Olivia Yolanda Pasaribu; Ade Pryta Simaremare; Joseph Partogi Sibarani (Universitas HKBP Nommensen, 2020)
Background : Garlic is a plant which is used to treat various types of diseases, especially the ones caused by bacterial infection. Allicin in garlic is one of the active compounds which has an antibacterial effect. Some studies found that garlic has an inhibitory effect on Salmonella typhi. Objective : This study aimed to determine the antibacterial effect of garlic juice against Salmonella typhi. Methods : This study was an experimental-laboratory research using disc diffusion method on MHA media. This study used five concentrations, namely 12.5%, 25%, 50%, 75%, and 100%. Amoxicillin and aquadest were used as positive and negative controls. The inhibition zone was determined by observing the clear zone around the disc then the results of the study were compared with positive control with CLSI 2017 guidance table where Salmonella typhi was susceptible when the amoxicillin inhibitory diameter zone was ≥ 17 mm, intermediate was 14-16 mm, and resistant was ≤ 13 mm. Results : The results showed that garlic juice has an antibacterial effect on various consentration. The minimum concentration of garlic juice to inhibit the growth of Salmonella typhi is on 50% with 19.25 mm diameters. Conclusion : There was an antibacterial effect of garlic juice on Salmonella typhi.